Islam di Indonesia Zaman Modern dan Kontemporer - Muhammad Basri; Juni Hati Hangoluan Siregar; Nurtia Sumarni Hasibuan (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
This research investigates the development of Islam in Indonesia within the context of the modern and contemporary era, with a focus on political, educational, and societal aspects. This research applies the literature study method with a qualitative approach to investigate the dynamics of Islam in Indonesia, particularly in the context of modern and contemporary Islamic practices. The focus of this study is to provide profound insights into the roles, challenges, and opportunities faced by Islamic organizations in shaping the social and political life in Indonesia. The findings reveal significant transformations in the role of Islam in politics, where Islamic parties actively engage in the democratization process..In the realm of education, there are efforts to integrate Islamic values with secular education, fostering a holistic educational environment. Islam in Indonesia also interacts with the ethnic, cultural, and religious diversity, playing a unifying role, although identity challenges emerge in an increasingly open and globally connected society. In conclusion, Islam in Indonesia undergoes complex dynamics, and inclusive approaches and interfaith dialogues are imperative to strike a balance between tradition, Islamic values, and the demands of modernity.